THE LONG TERM EFFECTS OF SULPHASALAZINE IN THE TREATMENT OF ANKYLOSING SPONDYLITIS; CLINICAL, LABORATORY AND SCINTIGRAPHIC STUDY - Hidayet Sarı,; Şansın Tüzün,; Ülkü Akarırmak,; İmdat Özkul,; İlhami Uslu, (Archives of Rheumatology, 2006)
Objective: We investigated the long term (1 year) effect of salazopyrine= sulphasalazine (SSZ) in 32 patient with ankylosing spondylitis (AS). Patients and Methods: Efficacy on clinical and laboratory findings and quantitative sacroiliac scintigraphy (QSS) changes were evaluated. Results: There was a statistically significant decrease in all clinical findings assessed by morning stiffness and night pain. Finger tip floor distance during lumbar anteflexion, chest expansion and lumbar Schober parameters and also laboratory findings like erytrocyte sedimentation rate improved after 1, 3, 6 ve 12 months of treatment with SSZ (p<0.01). In 15 patients, showing active sacroiliac joint inflammation according to sacroiliac index (SI index) in QSS, there was a significant decrease in SI index 6 months after treatment with SSZ (Right SI: p<0.05, Left SI: p<0.01). Conclusion: This decrease of progression of the disease activity in patients with ankylosing spondylitis during treatment with SSZ may show that SSZ prevents late complcations like ankylosis or provides long term remission in the activity of the disease. Finally, although the efficacy of SSZ in the patient with AS have been rather limited in recent studies, SSZ may be use as a disease modifying antirheumatic drug (DMARD) for patients with AS: (Rheumatism 2006; 21: 5-8)